The Relationship between Serum Selenium and Zinc with Gastroesophageal Cancers in the Southeast of Iran - Hashemi, Seyed Mehdi; Mashhadi, Mohamadali; Moghaddam, Alireza Ansari; Yousefi, Javad; Mofrad, Ahmad Dizangian; Sadeghi, Masoud; Allahyari, Abolghasem (Indian Journal of Medical and Paediatric Oncology, 2017)
Background: Selenium (Se) and zinc (Zn) have antioxidant and anticancer properties. Objective: The aim of this study was to evaluate the serum levels of Se and Zn and the correlation between the levels of these two elements with risk of incidence of esophageal cancer (EC) and gastric cancer (GC). Materials and Methods: In a case–control study, we selected sixty patients with GC or EC as the intervention group and 120 age-matched individuals as the control group. Exclusion criteria were the individuals with kidney and liver failure and the consumer of dietary supplements such as Se and Zn. Measurement of serum Se was done in a graphite furnace system and atomic absorption device of Varian and of serum Zn was done by a flame photometer system (flame) and atomic absorption device of Varian. Results: In thirty patients of ECs, 90% were squamous cell carcinoma and 10% adenocarcinoma, and out of thirty patients of GCs, 90% were intestinal type and 10% diffuse type. The level of two elements in cancer patients was lower than the control group (P < 0.05). There was no significant different between two cancer groups for level of Se and Zn, but there was a significant difference between the control group with two other groups. Conclusion: Our study confirmed the findings from previous prospective studies and randomized trials that reducing of lower levels of Se and Zn can effect on incidence of cancer.
Keywords: Case–control; esophageal cancer; gastric cancer; selenium; zinc